KI AGENG SURYOMENTARAM’S PHILOSOPHICAL VIEWS AND ITS RELEVANCE FOR POSTMODERNITY - Salamah, Umi Daris (Teosofia: Indonesian Journal of Islamic Mysticism, 2016)
Postmodern society has related to the terms of relativism, it is kind of the rejection of certain universal forms (grand narrative). In this case, the uncertainty of ethic is being one of the problems of humanity that exist in postmodern society. It implies that there is no true moral principle. The accuracy of all moral principles are relatively accommodated to the concerned or selected individual environment. The difficulty is how to marry such values to respect for diversity. Some agreements on the principles of social justice are desirable. Human has to position themselves between ‘absolutism’ and ‘anything goes’. Ki Ageng Suryomentaram, one of the Javanese Philosophers, formulated a set of philosophical views called to deal with human life. It is not an absolute concept to follow. Neither is it a form of totalitarianism reconstruction. Yet, it can be included as one of what so called by Lyotard as a small narrative. So in postmodernism view, the concept of Ki Ageng Suryomentaram, be it about harmony or manungsa tanpa tenger (human without signs), mawas diri (self-cautiousness), and mulur mungkret (state of being developed and shrunk) can be regarded as knowledge that qualifies to be publicized. It fits to some degree into a postmodern society for creating a harmonious life.